Concepts in Developing Learning Assessment Tools in the 21st Century: The Context of the Southern Border Multicultural Society - หะสีแม, อัรฟัน; เจะโซะ, อับดุลฆอนี; อาแซ, สะอาด; ราโอบ , อิสมาอีล (Al-HIKMAH Journal, 2023)
The purpose of this article is to explore the approaches for developing learning assessment tools in the 21st century within the context of the multicultural society in the southern border region. Based on the study, it is found that 1) Integration and Peaceful Coexistence: Blend curriculum with multicultural values for harmonious coexistence. 2) Diverse Assessment Tools: Deploy varied methods, aligning tasks with learners' context. 3) Multicultural Skills: Assess life skills, language proficiency, and desired attributes. 4) Reflective Growth Assessment: Mirror reality to foster individual growth. 5) Elevated Standards: Maintain high-quality evaluation instruments. And 6) User-Friendly Design: Ensure tools are intuitive, catering to tech-savvy users.